2021
DOI: 10.52628/87.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Medial pivot versus (cam post) posterior stabilised total knee arthroplasty, systematic review and meta-analysis of 3837 knees

Abstract: In the current literature, there is no consensus as to whether the medial pivot (MP) or posterior-stabilised (PS) knee provides the best result for the patient in the context of post-operative range of motion (ROM) and patient reported outcome measures (PROMs). The aim of this systematic review is to provide this equipoise with some clarity. We conducted this study following both the Preferred Reporting Items for Systematic Reviews and Meta-analyses Statement (PRISMA) and the Cochrane Handbook for systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
3
0
0
Order By: Relevance
“…Our observations showed no clear advantage for any of the groups regarding all these functional scoring algorithms. This finding corroborates with all four previous meta‐analyses but only for KSS [9, 24, 26, 38]. Contrary to our findings, two reviews reported significantly better WOMAC score for the MP knees [9, 24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our observations showed no clear advantage for any of the groups regarding all these functional scoring algorithms. This finding corroborates with all four previous meta‐analyses but only for KSS [9, 24, 26, 38]. Contrary to our findings, two reviews reported significantly better WOMAC score for the MP knees [9, 24].…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates with all four previous meta‐analyses but only for KSS [9, 24, 26, 38]. Contrary to our findings, two reviews reported significantly better WOMAC score for the MP knees [9, 24]. However, the mean difference value was less than the minimum clinically important difference (MCID) of 15 points [10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation